Exploiting the magnetoelectric effect in piezoelectric/conductor composites for sensing static magnetic fields. Issue 174 (1st September 2016) - Gaiotto, F. J.; Montanher, D. Z.; Nespolo, R. G.; Freitas, A. L. S.; Silva, D. M.; Pereira, J. R. D.; Santos, I. A.
ABSTRACT: In this work, static magnetic field sensors based on the interaction between the Lorentz force and the direct piezoelectric effect were developed and characterized. The major components of these solid-state sensors are a piezoelectric/conductor laminar composite, formed by a PZT-5A ferroelectric ceramic disk placed between two thin conductive silver layers, and a single coil to generate a controllable oscillatory magnetic field. Design parameters, such as the length and number of turns of the coil, were investigated, and a spatial field resolution of 0.24 Oe/mm was typically observed.